The Latvian Collections at the New York Public Library: A Historical Overview. (2nd October 2022) - Horbal, Bogdan
ABSTRACT: The NYPL's Latvian collection is one of the largest in North America. Herman Rosenthal, the first chief of the Slavonic Division, was born in what is now Latvia and laid a solid foundation for this collection. In the 1920s and 1930s, the NYPL had an exchange partnership with the Latvian State Library. The Library also holds Latvian materials published during post World War II years, both from the Communist-dominated homeland and those printed in the West. At present, the NYPL is the lead library when it comes to the development of the Latvian collection within the framework of ReCAP cooperative collection development.